2021
DOI: 10.1007/s00223-021-00886-5
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Osteoporosis: A Mendelian Randomization Study

Abstract: Observational studies suggest a link between depression and osteoporosis, but these may be subject to confounding and reverse causality. In this two-sample Mendelian randomization analysis, we included the large meta-analysis of genome-wide association studies for depression among 807,553 individuals (246,363 cases and 561,190 controls) of European descent, the large meta-analysis to identify genetic variants associated with femoral neck bone mineral density (FN-BMD), forearm BMD (FA-BMD) and lumbar spine BMD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 46 publications
(58 reference statements)
0
25
0
Order By: Relevance
“…These observational studies may be subject to confounding and reverse causality, which may affect the association between serum magnesium and osteoporosis/cardiometabolic diseases. Genome-wide association studies (GWASs) demonstrated that osteoporosis and cardiometabolic diseases were highly polygenic traits ( 24 29 ), and thus this two-sample Mendelian randomization (MR) study is intended to explore the causal relationship between serum magnesium and osteoporosis/cardiometabolic diseases, which benefits to prevent and treat these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…These observational studies may be subject to confounding and reverse causality, which may affect the association between serum magnesium and osteoporosis/cardiometabolic diseases. Genome-wide association studies (GWASs) demonstrated that osteoporosis and cardiometabolic diseases were highly polygenic traits ( 24 29 ), and thus this two-sample Mendelian randomization (MR) study is intended to explore the causal relationship between serum magnesium and osteoporosis/cardiometabolic diseases, which benefits to prevent and treat these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies reported that circulating adiponectin was associated with cardiometabolic diseases and osteoporotic fracture, but may suffer from confounding factors and reverse causality 9 – 14 . Their causal associations are not clear, and Mendelian randomization (MR) study has become one effective and powerful approach to explore the causal relationships between exposure phenotype and outcome phenotype 15 17 . Furthermore, two-sample MR analysis is able to greatly improve statistical power of MR study 17 – 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Their causal associations are not clear, and Mendelian randomization (MR) study has become one effective and powerful approach to explore the causal relationships between exposure phenotype and outcome phenotype 15 17 . Furthermore, two-sample MR analysis is able to greatly improve statistical power of MR study 17 – 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWASs) demonstrate that osteoporosis is one highly polygenic trait (17)(18)(19). Mendelian randomization (MR) study is effective and powerful to establish the causal relationship between exposure phenotype and exposure phenotype through using the GWAS summary statistics (20)(21)(22). These genetic variants are randomly allocated before birth and fixed at conception, and benefit to prevent reverse causation and potential confounding factors (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…The two-sample MR analysis has emerged as an important approach to greatly increase the scope and statistical power of MR based on the published summary data from GWASs (22,25,26). In this study, we use single nucleotide polymorphisms (SNPs) strongly associated with circulating bilirubin levels as the instrumental variables.…”
Section: Introductionmentioning
confidence: 99%